2023
DOI: 10.3390/ph16060868
|View full text |Cite
|
Sign up to set email alerts
|

The Outcomes and Adverse Drug Patterns of Immunomodulators and Thrombopoietin Receptor Agonists in Primary Immune Thrombocytopenia Egyptian Patients with Hemorrhage Comorbidity

Abstract: Immune thrombocytopenia (ITP) treatment has evolved recently. However, none of the treatments have only benefits without drawbacks. This study aimed to compare the clinical outcomes and adverse drug patterns of Eltrombopag, Romiplostim, Prednisolone + Azathioprine, High Dose-dexamethasone (HD-DXM) (control group), and Rituximab in primary ITP Egyptian patients. All patients were initiated with corticosteroids, HD-DXM, as a first-line treatment for the first month immediately following diagnosis. Four hundred s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 64 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…TPO-RAs had an encouraging impact on this study. The efficacy of TPO-RA in the first-line setting is not supported by sufficient evidence, according to recent studies [ 3 , 38 , 39 , 40 ]. These studies demonstrated that combining TPO-RAs and Dexamethasone is a potential first-line treatment for ITP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TPO-RAs had an encouraging impact on this study. The efficacy of TPO-RA in the first-line setting is not supported by sufficient evidence, according to recent studies [ 3 , 38 , 39 , 40 ]. These studies demonstrated that combining TPO-RAs and Dexamethasone is a potential first-line treatment for ITP.…”
Section: Discussionmentioning
confidence: 99%
“…Primary immune thrombocytopenia (ITP) is an autoimmune hemorrhage disorder characterized by impairment of platelet production and immunological abnormalities resulting in platelet destruction [ 1 ]. Severe internal bleeding can occur as a consequence [ 2 , 3 ]. ITP affects approximately 1 in every 20,000 individuals, with females being more affected than males [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [30], they propose Prednisone as a treatment for allergic rhinitis. In the case of hypertension, there are studies that relate the impact of Prednisone on this disease, but mainly in a negative way [50]. In [13], they already found that some of the predictions made were contraindications to the disease, as the included relations are too general.…”
Section: Prednisonementioning
confidence: 99%
“…Eltrombopag is a non-peptide thrombopoietin receptor agonist that promotes megakaryocyte growth [ 18 ]. Recent ITP studies reported that adverse events had happened during Eltrombopag use, such as thrombosis, liver cirrhosis, elevated liver enzymes, osteoporosis, pulmonary hypertension, plantar fasciitis, numbness, tingling, headache, dizziness, and fatigue [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%